Role of Dual-Specificity Phosphatase 1 in Glucocorticoid-Driven Anti-inflammatory Responses - Hoppstädter, Jessica; Ammit, Alaina J. (Frontiers in Immunology, 2019)
Glucocorticoids (GCs) potently inhibit pro-inflammatory responses and are widely used for the treatment of inflammatory diseases, such as allergies, autoimmune disorders, and asthma. Dual-specificity phosphatase 1 (DUSP1), also known as mitogen-activated protein kinase (MAPK) phosphatase-1 (MKP-1), exerts its effects by dephosphorylation of MAPKs, i.e., extracellular-signal-regulated kinase (ERK), p38, and c-Jun N-terminal kinase (JNK). Endogenous DUSP1 expression is tightly regulated at multiple levels, involving both transcriptional and post-transcriptional mechanisms. DUSP1 has emerged as a central mediator in the resolution of inflammation, and upregulation of DUSP1 by GCs has been suggested to be a key mechanism of GC actions. In this review, we discuss the impact of DUSP1 on the efficacy of GC-mediated suppression of inflammation and address the underlying mechanisms.